Genetic variability of human metapneumo‐ and bocaviruses in children with respiratory tract infections. Issue 1 (7th November 2013) - Pogka, Vasiliki; Moutousi, Afroditi; Kossyvakis, Athanasios; Kalliaropoulos, Antonios; Sgouras, Dionyssios N.; Giannaki, Maria; Mentis, Andreas F.
<x xml:space="preserve">Abstract</x> Objectives The genotypic analysis of human metapneumo‐(HMPV) and boca‐(HBoV) viruses circulating in Greece and their comparison to reference and other clinical strains. Design Genetic analysis of representative strains over three consecutive winter seasons of the years 2005–2008. Setting Representative positive specimens for HMPV and HBoV from paediatric patients of healthcare units and hospitals in Southern Greece with influenza‐like illness or other respiratory tract infections. Sample Seven to ten positive specimens for either HMPV or HBoV from each winter period. In total, 24 specimens positive for HMPV and 26 for HBoV, respectively. Main outcome measures Sequence diversity of HMPV and HBoV strains by sequencing the complete G and VP1/VP2 genes, respectively. Results In total, 24 HMPV strains were found to have a 92–100% nucleotide and a 85.9–100% amino acid identity. Phylogenetic analysis based on the number of amino acid differences, revealed circulation of 4 different subclusters belonging to genetic lineage B2. Similarly, analysis of 26 HBoV strains indicated that 22 clustered within genotype St2, 2 into genotype St1 and the remaining 2 formed a third cluster derived from potential recombination between different St1 genotype strains. St2 HBoV genotype was observed throughout the whole observation period whereas St1 only during the second and the third winter period. Higher levels of heterogeneity were observed between HMPV compared to HBoV strains. Conclusions Phylogenetic analysis revealed circulation of one single lineage (B2) for HMPV viruses and predominance of St2 genotype for HBoV viruses. A possible recombination between St1 genotype strains of HBoV was observed.